2015
DOI: 10.1186/s12944-015-0074-6
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the formation of cholesterol oxidation products in model systems using response surface methodology

Abstract: BackgroundCholesterol oxidation products (COPs) are produced during thermal processing of animal origin foods and are considered to have negative health impacts. The model systems are helpful to understand the impact of various factors on oxidation changes in foods during cooking process.MethodsThe study presented herein investigates the effects of pH, presence of unsaturated fatty acids, and heat on the formation of cholesterol oxidation products (COPs). Two model systems were designed to investigate the form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 35 publications
3
9
0
2
Order By: Relevance
“…(2005) reported a significantly higher COP concentration in aerobically stored raw, grilled, and roasted meat compared to their vacuum-packed alternatives. With pan roasting and oven grilling, high cooking temperatures are typically used and this causes a greater extent of cholesterol oxidation, affirming the results of Min et al . (2015) , which reported that higher cooking temperatures (>150℃) lead to an increased production of COPs.…”
Section: Resultssupporting
confidence: 77%
“…(2005) reported a significantly higher COP concentration in aerobically stored raw, grilled, and roasted meat compared to their vacuum-packed alternatives. With pan roasting and oven grilling, high cooking temperatures are typically used and this causes a greater extent of cholesterol oxidation, affirming the results of Min et al . (2015) , which reported that higher cooking temperatures (>150℃) lead to an increased production of COPs.…”
Section: Resultssupporting
confidence: 77%
“…As previously reported, this compound is formed in the first stage of oxidation [ 32 ]; however, egg cholesterol in the BSPE sample suffered three thermal treatments as pasteurization, spray-drying and the oven-cooking. According to literature data [ 5 , 36 ], 7-KC thermal stability is low if compared with other COPs, thus its degradation during these thermal treatments could be occurred, forming volatile compounds [ 29 ] and/or involving 7-KC in the formation of Maillard reaction products [ 37 ]. Among other COPS, also 7-β-HC decreased from BPE to BSPE sample (−27.7%); according to Min et al [ 36 ], this compound decreases during heating treatments.…”
Section: Resultsmentioning
confidence: 99%
“…In contact with air, cholesterol undergoes autooxidation, and the rate of the formation of cholesterol oxidation products depends mainly on storage conditions [ 38 ]. Studies have shown the significant effect of MDA concentrations on cholesterol synthesis in milk fat ( Fig 4 ).…”
Section: Resultsmentioning
confidence: 99%